ARABIC 2 SHEIKH NOMANI AND HIS APPROACH TO THE LANGUAGES OF THE QURAN: الشيخ النعماني ونهجه في "لغات القرآن" - Syed Hayat Ullah; Ahmed, Sardar; Ahmed, Khalil (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
Hazrat Maulana Allama Abdul Rasheed Nomani (May Allah have mercy on him)was endowed with many beautiful qualities and it can be said that Allah Almighty made him a perfect example of his power and all-round personality. Maulana Nomani was highly regarded by contemporary scholars due to his high moral character and scholarly ability. Maulana Nomani was undoubtedly a treasure trove of Islamic knowledge which was used by countless scholars, students and the general public,not only did he write on topics such as the difficulties of the Qur'an and the understanding and interpretation of the words of the Qur'an, but he also played an important role in bringing to light the hadith and especially the services of Imam Abu Hanifa (may Allah have mercy on him). He has written many books in which his “ Lughat-ul-Quran ” has the same status in Urdu as Imam Ragheb's “Mufradat-ul-Quran” has in Arabic. On the contrary, this book is a source for most of the dictionaries of the Qur'an written in Urdu language in terms of its writing style, references and comprehensiveness. Although there are other books on the subject of Quranic dictionaries and sources in Urdu language, but this book is of great importance in terms of its usefulness. That is why this book is equally useful not only for scholars and students but also for the general reader. For all these reasons, exposing Maulana's personality and his services in an investigative manner is a debt fulfillment as well as a fulfillment of a duty. For these reasons, I have chosen the topic for my research paper (Research and Critical Review of the Personality of Hazrat Maulana Abdul Rasheed Nomani and his book “Lughat-ul-Quran”)